Teaching content reading and writing - Ruddell, Martha Rapp (John Wiley & Sons, 2005)
With the passage of the "No Child Left Behind" act, and increasing pressures on teachers to produce results, true literacy is no longer optional. This book provides educators with the classroom tested theories and practices needed to rise to the demand of today's schools. They'll find discussions on issues that they face today in the classroom with respect to assessment and instruction. The sample lesson plans in each chapter will then help them to develop plans using specific instructional strategies.